2017
DOI: 10.1093/infdis/jiw555
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Innate Antiviral Immunity as Tools to Clear Persistent HIV Infection

Abstract: Human immunodeficiency virus (HIV) type 1 uses the CD4 molecule as its principal receptor to infect T cells. HIV-1 integrates its viral genome into the host cell, leading to persistent infection wherein HIV-1 can remain transcriptionally silent in latently infected CD4+ T cells. On reactivation of replication-competent provirus, HIV-1 envelope glycoproteins (Env) are expressed and accumulate on the cell surface, allowing infected cells to be detected and targeted by endogenous immune responses or immune interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 120 publications
1
23
0
Order By: Relevance
“…In vitro studies with laboratory-adapted, tier 1 HIV-1 strains showed that Env-specific nnAbs can direct ADCC/ADCVI (reviewed in (Ferrari et al, 2017)). However, little evidence exists to demonstrate Fc-mediated nnAb activity against primary HIV-1 isolates and transmitted/founder viruses (Bruel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies with laboratory-adapted, tier 1 HIV-1 strains showed that Env-specific nnAbs can direct ADCC/ADCVI (reviewed in (Ferrari et al, 2017)). However, little evidence exists to demonstrate Fc-mediated nnAb activity against primary HIV-1 isolates and transmitted/founder viruses (Bruel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from in vitro latency models supports the hypothesis that these reservoirs can be eliminated by combining latency reversal agents (LRAs), which induce the expression of viral antigens, with enhanced immune effectors, in a paradigm referred to as "kick and kill" or "shock and kill" (4-7). One strategy for harnessing immune effectors for this purpose is to target reactivated infected cells with HIV-specific antibodies, resulting in the engagement of natural killer (NK) cells, monocytes, and granulocytes, which eliminate infected cells through antibody-dependent cell-mediated cytotoxicity (ADCC) and/or antibodydependent cell-mediated phagocytosis (ADCP) (8)(9)(10). For this purpose, it will be crucial for the HIV-specific antibodies to bind to Env proteins expressed on the surfaces of the reactivated latently infected cells.…”
mentioning
confidence: 99%
“…This in turn triggers signaling through NFκB, IRF3/7, and MAPK pathways among others. Signaling through these well-studied pathways produces a host of pro-inflammatory cytokines, chemokines, and viral restriction factors to help combat early infection [14]. Importantly, myeloid cell responses to PRR activation can be tuned based on signaling from SLAMF1, SLAMF5, SLAMF7, SLAMF8, and SLAMF9 [15][16][17][18][19][20][21].…”
Section: Immune Responses To Viral Infectionsmentioning
confidence: 99%